Tổng hợp toàn phần ancaloit vincadiformin - Châu, Phan Đình (Vietnam Journal of Chemistry, 2014)
Based on the A. I. Scott,s hypothesis for biosynthesis of indole alkaloids in the plants, by the chemical methods we had succesfully total synthesized the3-oxo-vincadifformine (5) from 2-ethoxycarbonyl-tripthamine (2) via compound 3 and 3-oxo-secodine (4). With the intermolecular cyclisation of the key intermediate 4 the 3-oxo-vincadifformine (5) was formed and then by selective reduction of the C=O amide in compound 5 into CH2.group afforded vincadifformine (1).